ISLAMIC HUMANITARIAN PRINCIPLES AND MIGRATION: RECONSTRUCTION OF FORCED MIGRANT RIGHTS IN ISLAM - Agus Nilmada Azmi (UIN Raden Mas Said Surakarta, 2022)
This study aims to analyze the rights of forced migrants in Islam. Much Islamic literature, especially the Qur'an and the life history of the Prophets—starting from Prophet Abraham, Moses to Muhammad SAW- discusses the term migration and the importance of fulfilling various rights over them. However, this tradition is often ignored in the reality of modern world life, even though Muslim countries have accommodated about 50 percent of the world's refugee population. Based on qualitative descriptive approach by referring to written sources, especially the Qur'an, Sunnah, and the traditions of the early Muslim generation that talk about musta'min, the results of the study show that the Islamic tradition has provided a robust framework and the importance of paying attention to protection guarantees. For forced migrants, especially concerning fundamental rights, such as the right to dignity, non-refoulment, equal treatment, housing, health care, family reunification, and property. As a result, it is very essential for Muslims to re-open and maintain theological discourse on the issue of the protection of forced migrants. A move that can make an essential contribution to assisting Muslim countries in managing the crisis of forced migrants, in line with Islamic principles.